Inhibition of Nipah Virus Infection In Vivo: Targeting an Early Stage of Paramyxovirus Fusion Activation during Viral Entry - Porotto, Matteo (Public Library of Science, 2010)
In the paramyxovirus cell entry process, receptor binding triggers conformational changes in the fusion protein (F) leading to viral and cellular membrane fusion. Peptides derived from C-terminal heptad repeat (HRC) regions in F have been shown to inhibit fusion by preventing formation of the fusogenic six-helix bundle. We recently showed that the addition of a cholesterol group to HRC peptides active against Nipah virus targets these peptides to the membrane where fusion occurs, dramatically increasing their antiviral effect. In this work, we report that unlike the untagged HRC peptides, which bind to the postulated extended intermediate state bridging the viral and cell membranes, the cholesterol tagged HRC-derived peptides interact with F before the fusion peptide inserts into the target cell membrane, thus capturing an earlier stage in the F-activation process. Furthermore, we show that cholesterol tagging renders these peptides active in vivo: the cholesterol-tagged peptides cross the blood brain barrier, and effectively prevent and treat in an established animal model what would otherwise be fatal Nipah virus encephalitis. The in vivo efficacy of cholesterol-tagged peptides, and in particular their ability to penetrate the CNS, suggests that they are promising candidates for the prevention or therapy of infection by Nipah and other lethal paramyxoviruses.